2019
DOI: 10.1159/000496623
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Neuropsychological Studies in Panic Disorder Patients: Evidence of Impaired Performance during the Emotional Stroop Task

Abstract: Background: Recent investigations have highlighted significant differences in verbal recall between patients with panic disorder (PD) and controls. These studies have highlighted that verbal memory and working memory could be impaired in PD. Objectives: The objective of the present meta-analysis is to confirm this hypothesis, reviewing the studies that have investigated neurocognitive testing in PD. Methods: We performed a systematic literature search for studies published between 1980 and 2015 that reported c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…PCBT performance evaluating visuospatial memory of PD patients were found to be similar to those of healthy individuals. In a meta-analysis study, it was reported that while there was some evidence of neurocognitive impairment in PD, further study was needed to draw meaningful conclusions (40). It has been reported that the PCBT performance of PD patients was lower than that of healthy controls and that the visuospatial working memory learning process was poor (9,41).…”
Section: Discussionmentioning
confidence: 99%
“…PCBT performance evaluating visuospatial memory of PD patients were found to be similar to those of healthy individuals. In a meta-analysis study, it was reported that while there was some evidence of neurocognitive impairment in PD, further study was needed to draw meaningful conclusions (40). It has been reported that the PCBT performance of PD patients was lower than that of healthy controls and that the visuospatial working memory learning process was poor (9,41).…”
Section: Discussionmentioning
confidence: 99%
“…Manual searches were conducted in Journal of Anxiety Disorders, Psychiatry Research, and Google Scholar. To supplement these searches, we examined the reference sections of previous reviews related to anxiety disorders and EF (e.g., Harber et al, 2019;Lipszyc & Schachar, 2010). Additionally, a manual search was conducted in ProQuest Dissertations & Theses to capture unpublished literature.…”
Section: Search Strategymentioning
confidence: 99%
“…Сенситивные, перфекционистские черты личности, особенности семейного воспитания, отношений со сверстниками, необходимость поддержания высокого темпа деятельности в мегаполисах, недостаточная толерантность к стрессу и к высокой конкуренции способствуют формированию тревожных расстройств. Паническое расстройство (эпизодическая пароксизмальная тревога) -одно из наиболее распространенных пограничных психических заболеваний, характеризующиеся рецидивирующие приступы резко выраженной тревоги (паники), не связанные с какими-либо специфическими ситуациями или предметами, а, следовательно, непредсказуемыми и спонтанными [8, 26,32]. Частота его встречаемости среди городского населения составляет 7-12%, однако далеко не все пациенты обращаются за медицинской помощью.…”
Section: в помощь практикующему врачуunclassified